2006
DOI: 10.1007/s11085-006-9036-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Pre-Oxidation Treatment to Improve the Adhesion between Thermal Barrier Coatings and NiCoCrAlY Bond Coatings

Abstract: High-temperature coating systems, consisting of a Rene´N5 superalloy, a Ni-23Co-23Cr-19Al-0.2Y (at.%) bond coating (BC), and a yttria (7 wt%)-stabilized zirconia (YSZ) thermal-barrier coating (TBC), were thermally cycled to failure for seven different controlled pre-oxidation treatments and one commonly employed industrial pre-oxidation treatment to establish the preferred microstructures of the thermally-grown oxide (TGO) on a NiCoCrAlY bond coating after pre-oxidation. It was found that the failure of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 35 publications
(69 reference statements)
5
16
0
1
Order By: Relevance
“…This suggests that the VHT could, to a certain level, suppress the formation of mixed oxides during thermal exposure via developing a thin Al 2 O 3 layer in vacuum at high temperature. This is consistent with previous observations reported by many other researchers ( Ref 6,[11][12][13][14][15][16][17][18]. Similar to the as-sprayed TBC, cracking in the VHT TBC was very limited after up to twenty-five 100-h cycles (Fig.…”
Section: Oxidation Of Tbcssupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that the VHT could, to a certain level, suppress the formation of mixed oxides during thermal exposure via developing a thin Al 2 O 3 layer in vacuum at high temperature. This is consistent with previous observations reported by many other researchers ( Ref 6,[11][12][13][14][15][16][17][18]. Similar to the as-sprayed TBC, cracking in the VHT TBC was very limited after up to twenty-five 100-h cycles (Fig.…”
Section: Oxidation Of Tbcssupporting
confidence: 92%
“…Since oxidation of the bond coat has been recognized as the cause for separation of the ceramic layer from the substrate (Ref 2, 3, 7-10), the formation of the detrimental oxides may accelerate crack nucleation during thermal exposure, leading to premature TBC failure. Studies have shown that, when heat treated in low-pressure oxygen conditions, a continuous Al 2 O 3 layer may develop at the ceramic/bond coat interface in both thermally sprayed ( Ref 6,[11][12][13] and electron beam physical vapor deposited (EB-PVD) TBC systems (Ref [14][15][16][17][18]. Therefore, appropriate postspraying heat treatment(s) may suppress the formation of detrimental oxides by developing a TGO composed of a predominantly Al 2 O 3 layer, leading to improved TBC durability.…”
Section: Introductionmentioning
confidence: 99%
“…This strain energy increases with increasing TGO thickness. This explains that the failure of a high-temperature system can often be correlated with a critical TGO thickness at failure [6][7][8]. Thus, knowledge about the rate at which the TGO grows during service is necessary to predict the life span of the entire coating system.…”
Section: Introductionmentioning
confidence: 99%
“…The NiCoCrAlY coating shows a hightemperature resistance and oxidizes slowly. [14][15][16][17][18][19] Laser structuring was performed at the "Institute of Applied Material Physics--Applied Materials Physics" (IAM-AWP) 0 in Karlsruhe Institute of Technology (KIT), Germany. A micromachining workstation (PS450-TO, Optec, Belgium) was used which was equipped with an ultrafast Yb:YAG fiber laser (Tangerine, Amplitude Systems, France) operating at a maximum average power of 20 W and a maximum pulse energy of 100 mJ at 1 030 nm (TEM00 with M2 < 1.3).…”
Section: Structuring Of Small-sized Riblets On Coated In718mentioning
confidence: 99%